A parallel proposal for SEIR model using Cellular Automata - Casares, Facundo (2016)
Cellular Automata have been used with success in simulations of simples and complex systems belonging to different scientific areas, such as chemistry, biochemistry, economy, physics, etc.. In this work, we propose to use it in order to specify and implement a simulation model that allows to investigate behavioural dynamics for seasonal flu. This work presents a general solution where parallel programming techniques of shared memory are applied. Finally some experimental results about performance and flu behaviour are showed.